Elevated microRNA-21 Is a Brake of Inflammation Involved in the Development of Nasal Polyps - Liu, Ruowu; Du, Jintao; Zhou, Jiao; Zhong, Bing; Ba, Luo; Zhang, Jie; Liu, Yafeng; Liu, Shixi (Frontiers in Immunology, 2021)
Background: CRSwNP is an inflammatory disease that the mechanism is not fully understood. MiR-21, a member of miRNAs, has been reported to play roles in mediating inflammation. However, the expression of miR-21 and its role in patients with CRSwNP remain elusive. Methods: Turbinates from control subjects, uncinate processes from CRSsNP, polyp tissues from CRSwNP and nasal epithelial cells brushed from nasal mucosa were collected. The expression of miR- 21 and cytokines in nasal tissues and epithelial cells were detected by qPCR. The localization of miR-21 was detected by ISH, and its target was identified by bioinformation analysis, qPCR, IHC, WB and luciferase reporter system. The protein and mRNA of PDCD4 and NF-κB P65 were determined by WB and qPCR after miR-21 transfection in HNEpC. The role of miR-21 on cytokines was analyzed in HNEpC and nasal polyp explants. Results: MiR-21 was upregulated in CRSwNP relative to control subjects by qPCR, which was determined mainly in nasal epithelial cells of CRSwNP by ISH. Both pro-inflammation cytokines (IL- 1β, IL-6, IL-8, IL-25 and TSLP) and a suppressive cytokine (IL-10) were overexpressed in epithelial cells of CRSwNP. The expression of miR-21 was positively correlated with IL-10, and negatively correlated with IL-6, IL-8, IL-33 and TSLP in epithelial cells of CRSwNP. As a potential target of miR- 21, the expression of PDCD4 was negatively correlated with miR-21 in CRSwNP. In HNEpC, miR-21 could reduce the expression of PDCD4 at both mRNA and protein levels, and bioinformation analysis and luciferase reporter system confirmed PDCD4 as one target of miR-21. Furthermore, miR-21 could decrease the activation of NF-κB and increase IL-10 mRNA. Both SEB and LPS could elevate miR-21, with IL-25, IL-33, TSLP induced by SEB and IL-1β, IL-6, IL-8 induced by LPS, while the miR-21 could regulate the expression of IL-33, TSLP, IL-1β, IL- 6 and IL-8 in vitro and ex vivo. Clinically, miR-21 expression was inverse correlated with the Lund-Mackay CT scores and the Lund-Kennedy scores in CRSwNP. Conclusion: MiR-21 could be a prominent negative feedback factor in inflammation process to attenuate the expression of pro-inflammatory cytokines, thereby playing anti-inflammation role in CRSwNP.